APPLICATION OF PROBLEM BASED LEARNING MODEL TO STUDENT LEARNING OUTCOMES ON HEAT MATERIAL AND ITS TRANSFER - Ganien, Siona; Fauziah, Annuril Maulida (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
Students preparation to compete in 4.0 era based on curriculum implementation make it the teachers job to help students develop their problem solving skills, analytical process and critical thinking skills. It was necessary to have a supportive learning model, which is by choosing a problem based learning model. This article research used a problem based learning model in heat material and its transfer. The aim was to determine the implementation of learning, student learning outcomes and student responses after attending this lesson on heat material and its transfer. Types of research was a quasi-experimental research design, which is by one group pretest-postest design for 14 students of seventh grade junior high school. Research instruments used in this study was implementation observation sheets, pretest posttest and response questionnaire. The data analysis technique used in this study was observation sheet on the implementation of learning, n-gain and student response in questioning. The research results showed that the n-gain value was in high category, meaning there was a difference between pretest and postest scores and improved student learning outcomes.